(untitled) - Biehler, Gernot (New York, 2008)
Containing a synopsis of national bases of jurisdication (one of the first of its kind) international law is presented here through litigation. Legal procedures determine what the law is. The great variety of procedures which determine international law including diplomatic means are comprehensively examined. This perspective is original and helps to explain foreign policy expediences and conflicting prescriptive rules. Written as an academic study the book is also meant to benefit those practising in the field
Keywords: Procedures in international law,Thủ tục pháp lý quốc tế